Caracterização do chamado de alarme de Dasyprocta sp. e Cuniculus paca (Rodentia, Caviomorpha) em cativeiro - SILVA, João Gabriel Souza (Universidade Federal do Pará, 2019)
The social mammal present complex and sophisticate vocal behavior, they are able to send and receive precise information about the environment and the interactions of the group. The order Rodentia, the biggest among mammals, has species that developed wide vocal repertoire in order to intermediate both interspecific and intraspecific relationships. During threatening context, some rodents emit specific vocalizations classified as alarm calls, these calls allow the perception of the threat and the possibility of subsequent reaction such as fight or scape. These reactions in the context of threat provide to these rodent species an effective defense against predation. In this context, we described and compared the acoustic parameter of the alarm call of the agouti (Dasyprocta sp.) and the lowland paca (Cuniculus paca) using the sonographic analysis of their vocalizations recorded in captivity. We realized the register of the agonistic calls of 16 individuals of Dasyprocta sp. and 6 individuals of C. paca in the vivarium placed in the Federal University of Para in a total of 85 minutes of recording. We recorded alarm calls during the social interactions that happened in their respective cages. The bioacoustics analysis of the 539 alarm calls of the agouti demonstrate that the frequency bandwidth varies from 224 to 978 Hz and the duration is 898 ms. The 95 alarm calls of the lowland paca analyzed presented frequency bandwidth that varied from 340 to 1280 Hz, the mean of the call’s duration was 1967 ms. The sound characteristics of these so called indicated that there is a predominance of lower frequencies of the acoustic signal of the two species, but the pacas can reach high and low frequencies much larger than the agoutis, and issue of longer duration signals. The principal components analysis (PCA) revealed that the alarm calls of both species are differentiated primarily by the maximum duration and frequency of the beeps.